Quantum chemical investigation of electron delocalization patterns during photoexcitation in Fischer carbene complexes: a theoretical study - De Lange, Jurgens (University of Pretoria, 2021)
Dissertation (MSc (Chemistry))--University of Pretoria, 2020.